Utilization Of Ginger Rhizomes As Immune System Improvement During The Covid-19 Pandemic In Jati Village - Niknik Handayani; Anisa Sofiani Fima; Fajar J Nugraha; Indah Wulansari; Ira Sapartira Hidayati; Liza Rizky Ayunani; Yusri Aulia (Indonesian Journal of Community Empowerment (IJCE), 2021)
Abstract : Coronavirus Disease 2019, known as COVID-19, is something new and shocks the world, especially in Indonesia. This corona virus must be wary, because it spreads very quickly. In addition, the efforts are needed to increase the body's immune system, considering that viruses can enter the human body when the immune system decreases. The body's immune system is important to maintain during the current covid-19 period. One of the natural resources with low prices and contain high antioxidant is ginger rhizome. The Ginger Rhizome really helps the people in increasing the immune system. This community service activity was carried out in Jati Village by making ginger ‘wedang’ powder which was named "Rempah Pribumi " (indigenous spices). The purpose of this activity is to increase immunity and also the economy of the Jati villagers. Through this activity, it is hoped that the community of Jati village can create new innovations using the ginger rhizome to increase in the immune system during COVID-19 pandemic. Abstrak : Coronavirus Disease 2019 atau lebih dikenal sebagai COVID-19, merupakan sesuatu yang baru dan mengejutkan dunia, terutama di Indonesia. Virus corona ini merupakan virus yang harus di waspadai, karena penyebarannya sangat cepat. Di samping itu perlu upaya peningkatan sistem imun tubuh mengingat virus dapat masuk ke dalam tubuh manusia pada saat imun mengalami penurunan. Sistem imun tubuh penting untuk di jaga dalam masa covid-19 seperti saat ini, salah satu sumber daya alam dengan harga yang murah dan memiliki kandungan antioksidan yang cukup tinggi adalah rimpang jahe. Rimpang jahe ini sangat membantu masyarakat dalam meningkatkan sistem imun. Kegiatan pengabdian masyarakat ini dilaksanakan di Desa Jati dengan pembuatan serbuk wedang jahe yang diberi nama “Rempah Peribumi”. Tujuan diadakan kegiatan ini untuk meningkatkan imunitas dan perekonomian masyarakat Desa Jati. Melalui kegiatan ini diharapan masyarakat di Desa Jati dapat menciptakan inovasi baru sebagai peningkatan sistem imun di masa pandemi covid-19 berbahan dasar jahe.